2011
DOI: 10.1038/onc.2011.298
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of CD26 expression in epithelial cells and stromal cells during wound-induced skin tumour formation

Abstract: We have previously described InvEE transgenic mice in which non-dividing, differentiating epidermal cells express oncogenically activated MAPK kinase 1 (MEK1). Skin wounding triggers tumour formation in InvEE mice via a mechanism that involves epidermal release of IL-1a and attraction of a pro-tumorigenic inflammatory infiltrate. To look for potential effects on the underlying connective tissue, we screened InvEE and wild-type epidermis for differential expression of cytokines and immune modulators. We identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 32 publications
(47 reference statements)
0
42
0
Order By: Relevance
“…Prior experimental studies have evaluated dipeptidylpeptidases as targets for tumor therapy; however, these studies have been limited by their use of chemical inhibitors that block the activity of both DPP4 and FAP 36,37 . As a notable exception, one report showed that DPP4 is upregulated in a model of MEK1induced skin tumors and that treatment with sitagliptin delays malignant transformation 38 . Although that study suggests that DPP4 inhibition might be synergistic with interleukin 1 (IL1) receptor antagonist therapy, the authors do not consider a role for the regulation of lymphocyte trafficking.…”
Section: Discussionmentioning
confidence: 98%
“…Prior experimental studies have evaluated dipeptidylpeptidases as targets for tumor therapy; however, these studies have been limited by their use of chemical inhibitors that block the activity of both DPP4 and FAP 36,37 . As a notable exception, one report showed that DPP4 is upregulated in a model of MEK1induced skin tumors and that treatment with sitagliptin delays malignant transformation 38 . Although that study suggests that DPP4 inhibition might be synergistic with interleukin 1 (IL1) receptor antagonist therapy, the authors do not consider a role for the regulation of lymphocyte trafficking.…”
Section: Discussionmentioning
confidence: 98%
“…The overall picture that emerges from our studies of wound-induced tumor formation is of tumorigenesis via collaboration between multiple cell types and signaling molecules, including upregulation of IL-1α in differentiating keratinocytes driving increased expression of the dipeptidyl peptidase CD26 in fibroblasts (6, 8), recruitment of macrophages and other immune cells and a pivotal role of macrophages in both creating an immunosuppressive environment and stimulating keratinocytes to proliferate.…”
Section: Discussionmentioning
confidence: 99%
“…At least 2 regions per wound and animal were analyzed and a minimum of 3 mice used per data point. For quantifications using flow cytometry a 1.5 x 2 cm piece of back skin was harvested; dermal and epidermal cells were isolated as described previously (8) and labelled with the following antibodies: CD45-APC Cy7, CD3-PerCP (both BD), CD11b-PacBlue (Invitrogen), CD11b-AF594, MHC class II-brilliant violet 421 (all Biolegend), F4/80-PE, F4/80-alexa 647, Gr1-alexa 660 (RB6-8C5) and Ly6C-eF780 (all eBioscience). Labeled cells were sorted on a BD FACSARIA II cell sorter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A role of CD26/DPP4 in tumor biology has been suggested according to its functional and enzymatic properties in T cell lymphoma, mesothelioma, melanoma, renal carcinoma, colorectal cancer, and lung cancer [9][10][11][12][13][14][15]. Recently, a CD26/DPP4 antibody was employed as a therapeutic measure in mesothelioma and T-cell lymphoma showing down-regulation of RPB1 followed by inhibitory DNA binding of CD26/DPP4 [16][17][18].…”
Section: Introductionmentioning
confidence: 99%